Plasmodium Falciparum Identification in Thick Blood Preparations Using GLCM and Support Vector Machine (SVM) - Farah Zakiyah Rahmanti; Novita Kurnia Ningrum; Septian Enggar Sukmana; Prajanto Wahyu Adi (Universitas Dian Nuswantoro and IndoCEISS, 2017)
Malaria is one of the serious diseases that require rapid handling, otherwise it can lead to death. One of the causes of malaria parasites is plasmodium falciparum which can cause severe or fatal malaria. Handling a medical late can increase the risk of death. Therefore, it takes a rapid identification system with a high percentage of accuracy to reduce the risk of death. This research aims to build an identification system of plasmodium falciparum in thick blood film using Gray Level Co-occurrence Matrix (GLCM) and Support Vector Machine (SVM). The GLCM is used to get texture feature values such as contrast, correlations, energy, and homogeneity from images. Those values is processed and as an input of classification using SVM. The research result using SVM for accuracy value ofÂ plasmodium falciparum identification can reach 93.33%.